Pengaruh Market Value Added (MVA) dan Economic Value Added (EVA) terhadap Harga Saham dengan Return on Asset (ROA) sebagai Variabel Moderasi - Dwike Nabilla; Mariana Mariana (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to determine the influence of Market Value Added (MVA) and Economic Value Added (EVA) on stock prices, with Return on Asset (ROA) as a moderation variable. In the world of investment, stock prices are an important indicator that reflects the value of a company in the eyes of investors. Therefore, this study seeks to explore how economic added value and market value can contribute to an increase in stock prices, as well as whether a company's financial performance reflected in ROA can strengthen the relationship. The research method used is a quantitative method. The sampling technique was carried out by purposive sampling of 30 banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2022. The sample selection criteria include companies that consistently publish financial statements and have the complete data needed in this study. Data were analyzed using SPSS software version 26 with multiple linear regression analysis techniques to test the direct influence, as well as Moderated Regression Analysis (MRA) to test the role of ROA moderation. The results of the study show that MVA has a positive and significant effect on stock prices. The same goes for EVA, which also has a positive and significant influence on stock prices. However, when ROA was tested as a moderation variable, the results showed that ROA was unable to strengthen or weaken the influence of MVA on stock prices. The same is true of the influence of EVA on stock prices, where ROA has not proven to be a significant moderator. These findings indicate that while MVA and EVA are important indicators in determining stock prices, financial performance through ROA is not always able to moderate these relationships in the context of banking companies in Indonesia.